Chinese Consensus on Application Speifications for Noninvasive Positive Pressure Ventilation of Elderly Patients with Obstructive Sleep Apnea - Chinese Association of Geriatric Sleep Medicine, Chinese Geriatrics Society (Zhongguo quanke yixue, 2024)
Obstructive sleep apnea (OSA) is prevalent in the elderly population due to the weakened neuromuscular function of the upper airway and unstable respiratory regulation in the elderly. OSA is a risk factor for a variety of common chronic diseases, and affects cognitive function and multi-system organ function in the elderly. Therefore, it is essential to provide effective therapeutic interventions for OSA in the elderly. The Sleep Medicine Branch of the Chinese Geriatrics Society, as the initiator, organized domestic experts in related fields to repeatedly discuss the operation process, requirements, specific ways and methods of noninvasive positive pressure ventilation (NPPV) treatment for elderly OSA patients with reference to domestic and international clinical studies, and finally made this expert consensus, which is aimed at standardizing the treatment of NPPV in elderly OSA patients in China to provide a reference.